Ascending aortic replacement versus aortic root replacement in patients with type A aortic dissection involving the aortic root - Fausto Biancari; Giuseppe Gatti; Timo Mäkikallio; Tatu Juvonen; Giovanni Mariscalco; Zein El-Dean; Matteo Pettinari; Javier Rodriguez Lega; Andrea Perrotti; Francesco Onorati; Konrad Wisniewki; Till Demal; et al. (Therapeutic Advances in Cardiovascular Disease)
Background: Extensive surgical resection of the thoracic aorta in patients with type A aortic dissection (TAAD) is thought to reduce the risk of late aortic wall degeneration and the need for repeat aortic operations. Objectives: We evaluated the early and late outcomes after aortic root replacement and supracoronary ascending aortic replacement in patients with TAAD involving the aortic root. Design: Retrospective, multicenter cohort study. Methods: The outcomes after aortic root replacement and supracoronary ascending aortic replacement in patients with TAAD involving the aortic root, that is dissection flap located at least in one of the Valsava segments, were herein evaluated. In-hospital mortality, neurological complications, dialysis as well as 10-year repeat proximal aortic operation, and mortality were the outcomes of this study. Results: Supracoronary ascending aortic replacement was performed in 198 patients and aortic root replacement in 215 patients. During a mean follow-up of 4.0 ± 4.0 years, 19 patients underwent 22 repeat procedures on the aortic root and/or aortic valve. No operative death occurred after these reinterventions. The risk of proximal aortic reoperation was significantly lower in patients who underwent aortic root replacement (5.5% vs 12.9%, adjusted subdistributional hazard ratio (SHR) 0.085, 95% CI 0.022–0.329). Aortic root replacement was associated with higher rates of in-hospital (14.4% vs 12.1%, adjusted odds ratio 2.192, 95% CI 1.000–4.807) and 10-year mortality (44.5% vs 30.4%, adjusted hazard ratio 2.216, 95% CI 1.338–3.671). Postoperative neurological complications and dialysis rates were comparable in the study groups. Conclusion: Among patients with TAAD involving the aortic root, its replacement was associated with a significantly lower rate of repeat proximal aortic operation of any type compared to supracoronary aortic replacement. Still, aortic root replacement seems to be associated with an increased risk of mortality in these patients. Trial registration: ClinicalTrials.gov: NCT04831073 ( https://clinicaltrials.gov/study/NCT04831073 ).